Finishing Barn Cost Return Projection - Dhuyvetter, Kevin C.; Tokach, Mike D.; Jones, Rodney (My University, 1996)
This publication provides estimated cost and returns for a finishing barn.
MF2152_1996_10
Keywords: MF2152; Livestock; Economics; MF